Sixties radicalism and social movement activism : retreat or resurgence? - Jones, Bryn, 1946-; O'Donnell, Mike (Anthem world history., 2010)
Sixties Radicalism and Social Movement Activism' explores and re-analyses major events, debates and themes from the radical developments of the nineteen sixties and relates them to contemporary social movements and issues.